The Role of 5-HT1A Receptor in Cancer as a New Opportunity in Medicinal Chemistry - Corvino, Angela; Fiorino, Ferdinando; Severino, Beatrice; Saccone, Irene; Frecentese, Francesco; Perissutti, Elisa; Di Vaio, Paola; Santagada, Vincenzo; Caliendo, Giuseppe; Magli, Elisa (Current Medicinal Chemistry, 2018)
The 5-HT1A receptor is a pharmacologically well characterized serotonin receptor subtype and it has long been investigated because of its involvement in several physiopathological mechanisms and treatment of neurological diseases like ansia and depression. Serotonin (5-HT) also shows many non-neural functions such as essential hypertension, embryogenesis, follicle maturation and behavior. Moreover, it exerts a growth factor function on different types of non-tumoral cells, and it was also found to be related to oncogenes. In fact, growth-stimulatory activity of serotonin in different human tumor cells has been reported. Recently, new chemical molecules binding the 5-HT1A receptor have been described as novel therapeutic entities useful in neuroprotection, cognitive impairment, Parkinson's Disease, pain treatment, malignant carcinoid syndrome and cancer. It was widely demonstrated that 5-HT1A receptor is involved in the carcinogenesis and consequently in many human tumor types, such as prostate, bladder, small cell lung, colonrectal and cholangiocarcinoma. Furthermore, depending on the tumor type, 5-HT1A receptor antagonists were shown to be capable of blocking the 5HT-induced increase in tumor growth. In this review, we have focused our attention on each tumor type where the 5-HT1A receptor is involved, investigating the role of this molecular target and the different classes of compounds that have shown the capability to modulate it. The analyzed aspects could represent a hint for the medical chemists to develop novel molecules as selective 5-HT1A agents are useful in further elucidating the role of this therapeutic target.
Keywords: carcinogenesis